Аналіз художньої обробки зображень в програмному середовищі Adobe Photoshop - Єхало, А. А. (ХНУРЕ, 2024)
This work is dedicated to the general review of tools and methods for artis tic editing of graphic images available in the Adobe Photoshop software environment, considering their usage in the process of product creating in media production and entertainment industry. The review is based on the latest versions of the software (specifically Adobe Photoshop editions of 2020 – 2024 years). The work does not focus on technical aspects of the software but examines it from the perspective of various UI/UX interactions concerning digital content creators directly.
Keywords: Adobe Photoshop; обробка зображень